The space of the theater stage in the East and in the West - Hamza, Moayyad Shafeeq (project baikal, 2023)
In his lectures on conventional theater and the description of performance styles and scenery in Chinese and Japanese theaters, Meyerhold emphasized the need to learn from these theatrical styles and apply them. However, he warns that some of these styles are extreme. When is the landscape considered extreme? Does the mass perceive the same thing the same way in any place and at all times? What is the role of culture in the process of perception? Are there any differences in intellectual, educational and philosophical contexts that have created an influential human heritage in the East Asian view of the world, different from those that have crystallized to form the views of Westerners, which led to profound changes in art, theatrical form and content? and even at the level of its perception? This research aims to understand the public perception in different cultures in order to provide ideas for directors and set designers working in different places.
Keywords: conditional theater; theatrical scenery; theater of the East; Theatrical perception; Meyerhold